The 600-mm precipitation isoline distinguishes tree-ring-width responses to climate in China. Issue 2 (14th September 2018) - Liu, Yu; Song, Huiming; Sun, Changfeng; Song, Yi; Cai, Qiufang; Liu, Ruoshi; Lei, Ying; Li, Qiang
Abstract: The numerous temperature and precipitation reconstructions in China based on tree-ring-width data have played significant roles in furthering the understanding of past climate changes. However, the geographical variability in the responses of trees to climate variations in China remains largely undetermined. Here, we describe an important spatial boundary in the response of trees to climate variations, namely the 600-mm annual precipitation isoline. We found that, to the north of this line, tree-ring widths are usually positively correlated with precipitation and negatively correlated with growing-season temperature. To the south of this line, the tree-ring widths respond positively to temperature, and winter half-year temperatures are the main reconstructed parameters, especially on the third topographical step of China. We also found that precipitation reconstructions based on tree-ring data and the Palmer Drought Severity Index almost exclusively fall in the region of the 200- to 600-mm annual precipitation isolines, not other regions. Our findings indicate that, when using multiple tree-ring-width chronologies for large-scale past climate reconstructions, the climatic signal of each tree-ring-width series should be carefully considered.